PERAN KEPERCAYAAN PADA PEMASARAN INFLUENSER UNTUK MENINGKATKAN LOYALITAS MEREK (Universitas Muhammadiyah Palembang, 2023)
Purpose– This research aims to examine the direct and indirect roles of the relationship between the credibility and attractiveness of influencers on brand loyalty among young consumers in Indonesia, mediated by trust. Design/methodology– This research employs a quantitative explanatory approach with a non-experimental cross-sectional method aimed at examining the relationships between the proposed variables. The survey was conducted online using Google Forms, and respondents were selected using a non-random purposive sampling technique. The analytical tool utilized was SmartPLS version 3.2.9 Findings - The research results indicate that the factor of source credibility has no direct effect on brand loyalty. In contrast, attractiveness exhibits a significant positive relationship with brand loyalty. Additionally, influencer credibility and attractiveness are found to have a significant positive relationship with trust. Finally, trust demonstrates a significant positive relationship with brand loyalty. This research is expected to contribute to the existing literature on the role of influencers in marketing communication activities, particularly in terms of brand loyalty, for both academics and practitioners.